Fi Masadir al Turath al Siyasi al Islami: By Nasr Muhammad 'Arif (Arabic). Herndon, VA: International Institute of Islamic Thought, 1994, 237pp. (American Journal of Islam and Society, 1995)
This is perhaps one of the most useful books I have come across inrecent years. In an age when almost every Middle East or Islamic studiesspecialist is obsessed with "political Islam" or "radical or fundamentalistIslam," and when the western mass media and below-average media specialistson the Muslim world try to explain "the rage of Islam" to theiraudience, this book is a forceful reminder that the political language ofcontemporary Islamic revivalism is grounded in a historically establishedand rich Islamic (political) tradition. It also reminds us that in order to dojustice to the political principles of the modem Islamic movement, boththe academics and the media specialists must familiarize themselves withthis rich and historically constructed tradition.The author's primary intention is to document and discuss the mainsources (i.e., writings) of Islamic political thought from the first centuriesto the present. To 'Arif, the Islamic theory of knowledge and practice,which is based on the Qur'an and the Sunnah, has worked as a catalyst thatenabled the Muslim mind to construct a unique political theory that takesinto account changing sociopolitical and historical conditions. As a result,"political thought" has always formed the crux of Islamic thinking in generaland has never been divorced from the unique evolution and progressof Islamic civilization. What this means, in effect, is that for a modemscholar to carry out research, let us say, on the concept of jihad in Islam,he/she must trace the concept to its earlier sources and study it in its epistemologicaland historical evolutions. Concepts do change, depending on ...